The Durability of Durable Goods - Kleiman, E.; Ophir, T. (Review of Economic Studies, 1966)
Journal Article The Durability of Durable Goods Get access E. Kleiman, E. Kleiman The Hebrew University, Jerusalem Search for other works by this author on: Oxford Academic Google Scholar T. Ophir T. Ophir The Hebrew University, Jerusalem Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 2, April 1966, Pages 165–178, https://doi.org/10.2307/2974440 Published: 01 April 1966